Housing Wealth and Aggregate Consumption in Sweden - Jie Chen (Uppsala University, Department of Economics, 2006)
This paper extends the VECM cointegration model and PT (permanent-transitory) variance decomposition framework proposed by Lettau & Ludvigson (2004) and applies them on the Swedish data spanning from 1980q1 to 2004q4. There are strong statistical evidences that the movements of aggregate consumption, disposable income, housing wealth and financial wealth are tied together. However, it also suggests that the short run variations in the Swedish housing market are largely dissociated with consumer spending. Meanwhile, it is shown that the strength of the linkage between consumption and housing wealth is not sensitive to different model specifications and various measures of key variables.
urn:nbn:se:uu:diva-82799
Keywords: E21; E32; E44; R31; 330; housing wealth; consumption; wealth effect; VECM; PT decomposition; Wohneigentum; Einkommensverteilung; Vermögensverteilung; Verbraucher; Kointegration; Dekompositionsverfahren; Schweden